Exogenous and Endogenous Factors of Innovative Development of the Oil and Gas Corporations - BORGES, Ageu M.; SAKULYEVA, Tatyana N.; TULENBAYEV, Zhanat S.; KOZHAGELDI, Bolat Zh.; KARABASSOV, Rassul A. (Journal of Environmental Management and Tourism; Vol 11 No 5 (2020): JEMT Volume XI Issue 5(45) Fall 2020, 2020)
The paper investigates the factors and indicators of innovative development, considers their impact on the environmental management and improvement of the efficiency of innovation management of the oil and gas corporations. The purpose of the paper is to determine exogenous and endogenous factors and indicators of innovative development of the oil and gas corporation. The paper employs empirical, theoretical, and quantitative (statistical) research methods. As a result of the study, the authors determined an effective indicator calculated based on several indicators of innovative development; the factors of innovative development were identified and a connection between the factors of innovative development was proposed, proceeding from which, an approach to factor analysis of the indicators of innovative development of the oil and gas corporation in a certain restriction system (correlation system) was developed. The developed approach to factor analysis of innovative development indicators allows to adequately assess, analyze, and determine key indicators based on the effectiveness of innovation management to reduce high inappropriate costs for research and development (R&D) and optimize the business at large upon the introduction of high-tech solutions, innovative products and developments. This study can be applied in industrial sectors.